2021
DOI: 10.1016/j.heliyon.2021.e08614
|View full text |Cite
|
Sign up to set email alerts
|

Studies on electrode combination for COD removal from domestic wastewater using electrocoagulation

Abstract: Electrocoagulation is an electrochemical method that uses sacrificial electrodes to remediate wastewater. The combination of electrodes for the treatment of domestic wastewater is the factor that influences the removal efficiency of COD (Chemical Oxygen Demand) by using the electrocoagulation process. Aluminum and Iron electrodes are combined as anode-cathode and cathode-anode in Al–Al, Fe–Fe, Al–Fe, and Fe–Al. Different factors are considered to evaluate the removal efficiency of COD like; pH (3–9), reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…It could be shown that the Fe–Fe electrode combination provides the highest removal rate with 90% COD removal efficiency. [ 34 ] Taken together, several studies investigated the electrocoagulation process for domestic wastewater treatment, however, a direct comparison of batch and continuous system operation using the same electrode material is missing. This study has the potential to fill this gap in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…It could be shown that the Fe–Fe electrode combination provides the highest removal rate with 90% COD removal efficiency. [ 34 ] Taken together, several studies investigated the electrocoagulation process for domestic wastewater treatment, however, a direct comparison of batch and continuous system operation using the same electrode material is missing. This study has the potential to fill this gap in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…The biotreated wastewater was already characterized with a low COD load (90.6 mg/L) as compared with the primary clarified wastewater. Bote et al (2021) also reported comparable COD removal (67% -83%) efficiency from the domestic wastewater following 45 -60 minutes of electrocoagulation with Fe-Fe electrodes (12) . The electrocoagulation resulted in 79.5% and 87.9% removal of BOD from the primary clarified and biotreated wastewaters, respectively (Figure 2).…”
Section: Bod and Cod Removalmentioning
confidence: 90%
“…The above proves that the combination of electrocoagulation and ozonation is more effective compared to ozonation itself (Li et al 2013). In the electrocoagulation process, Aluminum hydroxide coagulants are formed from Al 3+ and OHand also Iron hydroxide derived from Fe 2+ and OHto destabilize pollutants in wastewater [21]. Likewise with the combination of electrocoagulation and ozonation, coagulants formed from electrocoagulation and reactive oxygen species derived from ozonation become intermediaries to remove pollutants both organic and inorganic [12].…”
Section: Codmentioning
confidence: 99%